2012
DOI: 10.1007/s11999-012-2309-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Carpal Tunnel Release Provide Long-Term Relief in Patients with Hemodialysis-Associated Carpal Tunnel Syndrome?

Abstract: Background Carpal tunnel syndrome (CTS) is a common complication in patients receiving long-term hemodialysis. In the short-term however, these patients are less likely to have pain relief and restoration of function after carpal tunnel release. However, it is unclear whether patients who have release for hemodialysis-associated CTS have differing persisting relief of symptoms compared with patients with idiopathic CTS. Questions/purposes We therefore compared (1) the severity of pain and level of function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…We also have found that pain and paresthesia, Paresthesias, the hallmark of neuronal involvement, may be caused by carpal tunnel involvement [14], nerve hypoxia due to ischemia by the A-V fistula [6] or by uremic neuropathy [15,16]. According to the literature carpal nerve syndrome is seen in 2% to 30% of patients [17,18] and may be due to limb edema caused by the A-V fistula or to deposition of Beta 2 amyloid [19].…”
Section: Discussionmentioning
confidence: 99%
“…We also have found that pain and paresthesia, Paresthesias, the hallmark of neuronal involvement, may be caused by carpal tunnel involvement [14], nerve hypoxia due to ischemia by the A-V fistula [6] or by uremic neuropathy [15,16]. According to the literature carpal nerve syndrome is seen in 2% to 30% of patients [17,18] and may be due to limb edema caused by the A-V fistula or to deposition of Beta 2 amyloid [19].…”
Section: Discussionmentioning
confidence: 99%
“…CTS affects 30-50% patients who have been on hemodialysis for over 10 years and over 80% patients who have been on hemodialysis for over 30 years. Specific factors contribute to the development of carpal tunnel syndrome in patients on chronic hemodialysis, including b2-microglobulin (b2-M) fiber deposits and arteriovenous (AV) fistula [5][6][7][8]. Malnutrition-inflammation-atherosclerosis syndrome is a common cause of increased mortality in chronic kidney disease [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is a frequent complication of patients undergoing hemodialysis. It often causes pain, numbness, tingling, or burning sensation in the median nerve distribution, hand weakness, and reduced quality of life 1,2,3. CTS in hemodialysis patients is recognized as an unremitting course, and surgical release procedures are often required after a long period of hemodialysis 4,5…”
Section: Introductionmentioning
confidence: 99%